PENGARUH JUMLAH WAJIB PAJAK TERDAFTAR, TINGKAT KEPATUHAN MENYAMPAIKAN SPT DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN PADA KPP PRATAMA TEGAL - Azizah, Meida Nurul; Sumarno, Mr.; Mubarrok, Abdulloh (PERMANA, 2018)
The effect of the number of registered taxpayers, compliance level in delivering SPT and tax audits to income tax receipts in Tegal Tax Service Office. Faculty of Economic and Bussines University Of Pancasakti Tegal 2018. The purpose of this research was to determine the effect of the number of registered taxpayers, compliance level in delivering SPT and tax audits to income tax receipts in Tegal Tax Service Office. The data analysis technique used for this research is descriptive and quantitative approach. The research used secondary data and more focused on the realization statements Number of registered taxpayers, compliance level in delivering SPT, tax audits and income tax receipts research sample that is the period of 2015-2017. The data collected were processed using SPSS software program. The statistical method used to test the hypothesis is multiple linier regression analysis. The result showed that the number of registered taxpayers has a positive and significant impact on income tax receipts. However compliance level in delivering SPT and tax audits not impact on income tax receipts.Keywords : Income tax receipts, The number of registered taxpayers, Compliance level in delivering SPT and Tax audits.